2020
DOI: 10.3389/fpsyg.2020.558520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occupational Fatigue on Cognitive Performance of Staff From a Train Operating Company: A Field Study

Abstract: Background: Occupational fatigue is a key issue in the rail industry that can endanger staff, passenger, and train safety. There is a need to demonstrate the relationship between workload, fatigue, and performance among rail staff. Objective: The present study, conducted in the workplace in realistic situations, integrating both subjective and objective measurements, aimed at demonstrating the relationship between workload, fatigue, and cognitive performance with a rail staff sample. Methods: The "After-Effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…7 Studies in the workplace have clearly established a relationship between cognitive fatigue and impaired performance, including slower reaction times, 8 reductions in concentration 9 and impaired memory and information processing. 10 This has extensively been researched amongst pilots 11 and train operators, 12 clearly demonstrating that cognitive fatigue is associated with decreased overall performance and safety. This has vital consequences, especially in professions which require a very low margin of error to maintain safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Studies in the workplace have clearly established a relationship between cognitive fatigue and impaired performance, including slower reaction times, 8 reductions in concentration 9 and impaired memory and information processing. 10 This has extensively been researched amongst pilots 11 and train operators, 12 clearly demonstrating that cognitive fatigue is associated with decreased overall performance and safety. This has vital consequences, especially in professions which require a very low margin of error to maintain safety.…”
Section: Introductionmentioning
confidence: 99%
“…Even studies amongst drivers revealed that cognitive fatigue accounted for 12% of car crashes and 10% of near-misses. 12 , 13 Amongst surgeons, level one evidence is lacking but the impact of cognitive fatigue and impaired performance on patients could be critical. Indeed, whilst there is significant heterogeneity in the literature, several studies have shown fatigue can result in increased surgical errors and adverse patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…They report higher mental fatigue than physical fatigue [23]. The central role of fatigue in impairing their work performance has been supported by research using subjective measures, objective measures, or both [23,24,25,26]. In China, healthcare workers were listed as one of the most vulnerable work populations to occupational fatigue, followed by taxi drivers and police officers [27].…”
Section: Occupational Fatiguementioning
confidence: 99%
“…A driver seated for too long and exposed to full body vibration is prone to fatigue and back problems (Wang et al, 2017;Park et al, 2020) Fatigue is one of the factors causing accidents in the transportation sector (Zuraida and Abbas, 2020). It can affect the safety behavior of bus drivers and their cognitive abilities and is associated with occupational safety factors (Fan and Smith, 2020). Adam and Jalil argued that the main point of contact for the WBV transmission to the driver is via the vehicle seat, originating from the engine when the vehicle is running.…”
Section: Introductionmentioning
confidence: 99%